The Psychological Interpretation of the Grieving Process - KIRÁLY, Lajos (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
This paper presents the psychological interpretations of the grieving process and examines how professionals from Sigmund Freud, Melanie Klein, Erich Lindenmann, Gerard Caplan, Alaine Polcz, and Emőke Bagdy through Erwin Ringel to Sara Bodó have interpreted grief. We find that all of them include in their definitions the concept of loss, which is “a reaction to the loss of a loved one or an abstraction that has taken place”. We then examine the differences between male and female grief, the ambivalent feelings associated with the fact of death, and the family dynamics that all testify to the family as the primary support when experiencing grief, pain,[1] and loss. In what follows, I will write about the linear stages of the grieving process: anticipation, shock, controlled and awareness stages, along with stages of uprising emotions, search and separation, and adaptation. [1] There are two types of pain in the literature: phasic pain and tonic pain, which are mediated by separate neural pathways in the brain. Melzak, Ronald (1990): The Tragedy of Needless Pain. In: Scientific American. 262, 2. 27–33.